Experimental Investigation of Concrete Characteristics Strength with Partial Replacement of Cement by Hybrid Coffee Husk and Sugarcane Bagasse Ash - Muliye Tarekegn; Kabtamu Getachew; Goshu Kenea (Advances in Materials Science and Engineering)
Concrete is the most extensively utilized construction material globally and is increasingly used due to industrialization and urbanization. Currently, most scientists worldwide are concentrating their attention on effective strategies to adopt materials from large amounts of waste resources as a partial substitute for cement in concrete production due to scarcity of resources and continuous environmental pollution. In this study, an experimental investigation was conducted on the properties of concrete made from the partial replacement of cement by hybrid coffee husk ash (CHA) and sugarcane bagasse ash (SCBA). The study considered different percentages (0%, 5%, 10%, and 15%) of hybrid ash to assess the engineering properties of fresh and hardened concrete of C-20/25. A slump and compaction factor test was conducted to study the workability of fresh concrete. The study showed that, as the percentage of replacement increased from 0% to 15%, the workability of the concrete decreased up to 15.15%. In addition, compression, split tensile, and flexural tests were done on the 7th, 14th, and 28th days to investigate the properties of hardened concrete. Based on the test result, 10% of hybrid ash was the maximum percentage of replacement that showed a compressive and tensile strength greater than the target strength. Therefore, the study concludes that up to 10% replacement of cement by hybrid ash may be employed in concrete production, which in turn is used to minimize the cost of construction and environmental pollution by recycling waste coffee husk and sugarcane bagasse.